The Multiple Ligament Injured Knee A Practical Guide to Management - Fanelli, Gregory C. (Springer New York : Imprint: Springer, 2013)
The Multiple Ligament Injured Knee, Second Edition is the definitive text on the successful diagnosis and treatment of multiple ligament knee injuries. Dr. Gregory C. Fanelli has once again recruited an international group of experts to create a reference suitable for orthopedic surgeons, trauma surgeons, sports medicine fellows, orthopedic surgery residents, physical therapists, physician assistants, and all health professionals who treat traumatic injuries of the knee. Vastly expanded from its first publication, new topics in this edition include:   -ACL based multiple ligament knee injury -Mechanical graft tensioning -Fracture dislocations -Articular cartilage restoration -Meniscus transplantation -Extensor mechanism restoration   The book was designed to be read either by chapter or sequentially to facilitate personal exploration of the topic. Hundreds of illustrations and photographs facilitate easy comprehension of the text. Covering everything from anatomy and biomechanics through diagnosis, classification, both non-surgical and surgical management, complications and selected case studies, The Multiple Ligament Injured Knee, Second Edition, gives a complete picture of a complex pathologic entity.